Dhat Syndrome as a Manifestation of a Culture-Bound Syndrome - A Case Report - Devaraj, Navin Kumar (Central Asian Journal of Medical Sciences, 2018)
Objectives: Dhat syndrome is one of the culture-bound syndromes related to fear of death due to loss of semen, common in India but extremely rare outside of India. This case report looks at a rare case of Dhat syndrome that presented to a primary care physician in Malaysia. Methods: This case report depicts the treatment approach used in this culture-based syndrome as compared to other culture-based syndrome such as Koro syndrome which is common in China and Southeast Asia. Results: The management in this case was mainly non-pharmacological, with reassurances, support and counselling given regarding the benign nature of this illness. Conclusion: Dhat syndrome management is challenging and may need a combination of both pharmacological and non-pharmacological treatment, including drugs, psychotherapy and counselling.